Pengaruh Jumlah Wisata, Kunjungan Wisatawan Dan Hotel Terhadap Pendapatan Asli Daerah Blitar - Nabila, Izzatun; Rachmawati, Lucky (Universitas Negeri Surabaya, 2023)
Each community will endeavor to boost its economy by making the most of its numerous economic facets, including the tourist industry in terms of attractions, visitor volume, and hotel capacity. The purpose of this research is to determine, between 2005 and 2022, how the number of hotels, the number of visitors, and the number of hotels in Blitar Regency effect the total revenue generated into the region. Multiple linear regression methods were used in this analysis. Using E-Views 12, we found that the number of attractions has a positive but not statistically significant effect on regional own-source revenue, as do the number of visitors and the total number of hotels in the region. Regional income is positively and statistically significantly impacted by all of these elements.